ASSISTANCE IN APPLYING FOR A NIB FOR MICRO BUSINESSES IN NARMADA SUB-DISTRICT - Putri, Dina Soes; Asmawati; Hidayah, Nurul; Ariansyah; Ariani, Zaenafi; Surmini (STKIP Citra Bakti, 2025)
It is imperative that every MSME actor is in possession of a Business Identification Number (NIB), which serves as a business identity and is legally recognised. Although the process of issuing NIBs has been streamlined and made more efficient through online platforms, a significant number of MSME players have yet to register. This is due to the fact that not all business actors are proficient in accessing technology, particularly those of an advanced age who are geographically dispersed across a number of regions. The objective of this service activity is to provide guidance on the importance of business legality (NIB) and to offer assistance with NIB registration for business actors in Narmada District, West Nusa Tenggara Province. This service employs the Participatory Action Research (PAR) method, wherein partners (participants) assume an active role in the activity. The partners of this activity are micro, small and medium-sized enterprises (MSMEs) assisted by the West Lombok 'Aisiyyah Regional Leadership (PDA) in the Narmada District area. The service activity is comprised of five discrete sessions, namely a pretest, a presentation of material pertaining to the urgency of business legality for MSMEs, a discussion of food safety and halal food, a posttest, and assistance in the application process for NIB. To conclude, there has been an increase in the level of awareness among partners with regard to the urgency of business legality, and an increase in the number of MSMEs that have NIB. Initially, the number of MSMEs that had NIB constituted only 33% of the total activity participants; however, by the conclusion of the service, the number of MSMEs with NIB had increased to 66%. In order to pursue further community service activities, it is necessary to assist in applying for PIRT and applying for MUI halal certification. This will help to complete partner business licensing, with the aim of increasing sales turnover.